TAMAN KOMUNITAS DENGAN PENDEKATAN GREEN ARCHITECTURE DI KOTA SOLO - Alvinda Saraswati; Musyawaroh Musyawaroh; Hari Yuliarso (Universitas Sebelas Maret Surakarta, 2016)
Public space is an urban facility that serves as a forum for interaction and recreational activities of the community. However, the existence of Solo City’s public space which serves as an area of interaction, recreation society and urban green space become degraded. Until 2014 Solo City’s public green space reached 12.02% of the total is to be achieved by 20%. The impact of vandalism of Solo City’s public space reducing facial aesthetics and lowering the interest of the public to visit. As a problem-solving strategies, takes a public space planning that can accommodate recreational activities and community interaction and optimize its potential as a green open space that can preserve environmental sustainability. With the phenomenon of people's appreciation of community interest and talent of Solo City is high enough, it can be a potential concept of public space that can accommodate groups of community interaction and public recreation. The formulation of the problem in this design is how to plan and design a community park as efforts increase green open space that can accommodate groups of community interaction and recreation community in Solo with Green Architecture approach . Thus it can be formulated Taman Komunitas planning objectives aligned with the Rencana Strategis (RENSTRA) Dinas Tata Ruang Kota Surakarta Tahun 2011–2015 to realize the addition of green open space which serves as the lungs of the city at the same time facilitate the activities of community interaction and recreation . Tangible public space planning to optimize its potential as a park with green open spaces are supported by a strategic approach to the concept of Green Architecture in order to achieve the target. The applied aspects of Green Architecture refers to the Greenship criteria set by the Green Building Council Indonesia. Four of these aspects include the right of land use, efficiency and energy conservation, water conservation, and health and comfort in the room. The application appears in the planning aspects of the design which utilizes the natural potential include the use of green roof , green walls , environmentally friendly materials , as well as planning refers to the Greenship benchmark..